Analysis of Business Incubators in Vocational High Schools in Building Student Business Start-Ups (Study on Vocational High Schools in Mojokerto Regency) - Alfiyah Mu'arofah; Sukarsih Sukarsih; Sudarmiatin Sudarmiatin; Rizky Firmansyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the role of business incubators in State Vocational High Schools (SMKN) in building student business start-ups in Mojokerto Regency. Business incubators in SMKN have great potential to encourage the development of students' entrepreneurial skills through training, mentoring, and access to business resources. The research approach used is qualitative with a case study method, involving the principal, incubator manager, entrepreneurship teacher, and students as research subjects. Data collection techniques were carried out through in-depth interviews, observation, and documentation. The results of the study indicate that business incubators in SMKN act as the main facilitators in improving students' skills and motivation to start a business. Supporting factors for the success of the program include school support, cooperation with the business world, and adequate facilities. However, several challenges were also identified, such as limited funds, human resources, and low student participation. However, the existence of business incubators has had a positive impact on students' readiness to establish start-ups, as seen from the success of several students in developing independent businesses. This study concludes that optimizing business incubator programs requires increased financial support, strengthening partnerships with the industrial world, and integrating practice-based entrepreneurship curriculum. The recommendations of this study are expected to be a reference for SMKN managers and other stakeholders to improve the effectiveness of business incubator programs in producing a competent generation of young entrepreneurs.